A novel scheme for the reporting of adverse drug reactions. Issue 4 (1st April 2001) - Clarkson, A; Ingleby, E; Choonara, I; Bryan, P; Arlett, P
Abstract : BACKGROUND: The safety of medicines used in children is of considerable public interest, yet available data to monitor the safety of medicines in children is limited. AIMS: To raise awareness and stimulate reporting of adverse drug reactions (ADRs) in children in the Trent region. METHODS: A pilot Paediatric Regional Monitoring Centre (PRMC) has been established in the Trent region. The scheme operates as an extension of the UK's spontaneous reporting scheme, the Yellow Card Scheme run by the Medicines Control Agency and the Committee on Safety of Medicines. Proactive interventions including a monthly reminder letter and presentations to staff in the identified hospitals have been made. RESULTS: During the first year of the PRMC, 95 reports were received from the Trent region compared to 40 for the previous year. Twenty four of these reports were for medicines used "off label". The 95 reports involved 105 drugs and 171 suspected ADRs. Twenty six of the ADRs (15%) were considered medically significant. CONCLUSIONS: The number of ADR reports from the Trent region has increased considerably in the first year of the scheme. The results show that intensive education and promotion of ADR reporting can result in a major increase in reporting. This initiative will increase our knowledge about the safety of medicines used to treat children and so help protect public health.